PENGARUH SEKTOR RIIL DAN KEUANGAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2007-2014 - Cahyaningrum, Ina Sholati (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Abstract: The research objectives of this research are to examine signifcant infuence of real sector of manufacture industry, real sector of trade, hotel, and restaurant, syariah fnance of syariah bank and syariah fnance of payment bank of syariah community to the growth of economy in Indonesia whether partial or simultan. The rsearch was used quantitative approach which used associative research. The taking of sample used nonprobability sampling technique and purposive sampling tehnique. The data used are secunder data which are gotten by triwulan data of gross domestic bruto based on constant price and from statistic report of syariah bank in year 2007-2014. The data accumulation are documentation and document study. The research was used method of clasic assumptsion experiment analysis, the experiment of doubled linier regression, hypotheses experiment, and the experiment of determination coefsien. The result of the reaserch showed that partially (individually), the syariah fnance of syariah bank infuenced positively and signifcantly to the growth of economy in Indonesia and syariah fnance of syariah bank and syariah fnance of payment bank of syariah community infuenced positively and signifcantly to the growth of economy in Indonesia. Meanwhile, simultaneously (collective) between the fnancial of syariah bank and syariah fnance of payment bank of syariah community infuenced signifcantly to the growth of economy in Indonesia. For variable of real sector in manufacture industry and real sector of trade, hotel and restaurant statistically couldn’t be continue, because in data excemination showed that there was problem of Multikolinieritas. So, the researcher took an action to delete variable which by Multikolinieritas by the reason if that problem was solred by using PCA prosedure. There is only one factor which represented all of free independent variable, so when picturing the similarity of factor regretion could be represented of each free variable to dependent variable, because it could not be seen which variable having the positive connection and which variable having negative connection to dependent variable.Keywords: Real Sector, Syariah Finance, and Economy Growth